Availability of Facilities and Infrastructure to Improve the Quality of Jurisprudence Learning - Rofiatul Hosna; hana halfazila (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Facilities and infrastructure are important components in supporting the learning process that must be present in schools. This research aims to see how far facilities and infrastructure can improve the quality of student learning at Madrasah Tsanawiyah Madrasatul Quran Tebuireng Jombang. Data was taken through observation, interviews and documentation. The results obtained after conducting this research are the availability of facilities and infrastructure at Madrasah Tsanawiyah Madrasatul Quran, what is the quality of Fiqh learning at Madrasah Tsanawiyah Madrasatul Quran, and the availability of facilities and infrastructure that can improve Fiqh learning at Madrasah Tsanawiyah Madrasatul Quran. This research aims to find out the quality of Islamic jurisprudence learning at the Madrasah Tsanawiyah Madrasatul Qur'an Tebuireng Jombang, what is the availability of facilities and infrastructure at Madrasah Tsanawiyah Madrasatul Quran Tebuireng Jombang, and how is the availability of facilities and infrastructure in improving the quality of Islamic jurisprudence learning at Madrasah Tsanawiyah Madrasatul Qur'an Tebuireng Jombang.